Black Rose Alice. 05 - Mizushiro, Setona, 1971-; Werry, John (Translator) (Viz Media, 2015)
"Dimitri Lewandowski is a celebrated tenor in early 1900s Vienna. When he is killed in an accident, his corpse is colonized by the seeds of a vampire master. At first, Dimitri denies that anything has changed, but as the people around him start dying, he is forced to accept the ghastly truth. Dimitri Lewandowski is a celebrated tenor in early 1900s Vienna. When he is killed in an accident, his corpse is colonized by the seeds of a vampire master. At first, Dimitri denies that anything has changed, but as the people around him start dying, he is forced to accept the ghastly truth. Flash forward to 2008. In Tokyo, Alice thinks she has fully adapted to her role in Dimitris nest and is carefully considering which vampire to propagate with. But when the man she loved when she was Azusa shows up one day, her carefully constructed acceptance starts to crumble"--page 4 of cover.